Restitution of indigenous ancestors, uncomfortable heritage, and ways of seeing violence in Argentina - Crespo, Carolina Flavia (2022)
The indigenous demands made in Argentina in recent decades for the restitution of their ancestry to museums and other institutions have given rise to the making of several films and photographic exhibitions. The aim of this paper is to reflect on these images as "ma-chinery for the production of sensibilities", examining the politics of light in the representa-tion and administration of violence and the affects and effects they have on the reconstruc-tion of a past that demands justice on the part of the original peoples. I examine the images dedicated to making public the violence and racism involved in these heritagization process-es and the implications, discomforts and positionings that these disturbing memories gener-ate among the Mapuche in Patagonia, in order to discuss the category of "uncomfortable", "dissonant" or "difficult heritage", as heritage linked to exercises of human rights violations has been defined.